Principles of emergency management and emergency operations centers (EOC) / Michael J. Fagel, PhD, CEM. - Michael J Fagel (Boca Raton, FL : CRC Press, 2011)
Assessing vulnerabilities / Michael Fagel -- Developing a planning team / Michael Fagel -- Responder health and safety / Michael Steinle -- Disaster preparedness and the law / Thomas Schneid -- Stress management and responders / K. R. Juzwin -- Developing an emergency operations plan (EOP) / Michael Fagel -- Developing an exercise program / Michael Fagel -- Three types of exercises / Michael Fagel -- EOC management and operations / Lucien Canton and Nicholas Staikos -- ICS/EOC interface / Michael Fagel -- Continuity of operations planning / Chad Bowers -- The role of business continuity management / Robert Coullahan.
Keywords: Emergency management